Profile of Students' Visual Thinking in Understanding and Applying Derivative Concepts - Darmadi; Nartini; Soleh, Dwi Rohman (International Journal of Applied Educational Research (IJAER), 2023)
The aim of this research is to obtain students' visual thinking profiles in understanding and applying derivative concepts. Qualitative research methods are used with the steps determining the subject, developing questions, collecting data, interpreting, presenting, reducing, categorizing, coding, and triangulating data, analysing data, and drawing conclusions. The subjects of this research were students of the mathematics education study program of PGRI Madiun University. At first, students understand the concept of derivatives without using visual thinking skills. Students understand the concept of derivative as a demotion. After learning, students understand the concept of derivatives with images as visualization. Students apply the concept of guidance without using visual thinking. After learning, students can apply derivative concepts by using images as visualization. Students understand that they must apply derivative concepts and explain with pictures or graphs. Students plan by analysing and then using function graphs to explain it. Students carry out plans by calculating analytically and completing explanations using pictures or graphs. Students check again by paying attention to the answers from friends beside them and discussions with the lecturer.